2017
DOI: 10.1016/j.labeco.2017.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Productivity effects of air pollution: Evidence from professional soccer

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
99
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(106 citation statements)
references
References 24 publications
5
99
1
1
Order By: Relevance
“…Air pollution has been found to increase students' absences (Currie et al, 2009) and their cognitive performances and test scores (Lavy, et al, 2014). It also has negative effects on short-run performance of outdoor athletic participants including soccer players (Lichter et al, 2015), marathon runners (Fu and Guo, 2016), and baseball umpires (Archsmith et al, 2016).…”
Section: Pollution and Productivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Air pollution has been found to increase students' absences (Currie et al, 2009) and their cognitive performances and test scores (Lavy, et al, 2014). It also has negative effects on short-run performance of outdoor athletic participants including soccer players (Lichter et al, 2015), marathon runners (Fu and Guo, 2016), and baseball umpires (Archsmith et al, 2016).…”
Section: Pollution and Productivitymentioning
confidence: 99%
“…However, because these studies rely on the exogeneity of air pollution as an identification strategy, they focus on narrow groups of workers in particular occupations such as fruit picking (Graff Zivin and Neidell, 2012), pear packing (Chang et al, 2016a), call center services (Chang et al, 2016b), garment assembly (Adhvaryu et al, 2014a) or a few firms in textile assembly (He, Liu et al, 2016). Air pollution has also been found to negatively impact short-run productivity of outdoor sports personnel including soccer players (Lichter et al, 2015), marathon runners (Fu and Guo, 2016), and baseball umpires (Archsmith et al, 2016). While these estimates are useful for evaluating narrowly-targeted environmental policies or evaluating the costs and benefits for small groups of people, their external validity is of concern in evaluating broad-based pollution reduction policies.…”
Section: Introductionmentioning
confidence: 99%
“…measures, and exposure levels. Recent work has linked exposure to ozone with reductions in the productivity of agricultural workers (Graff Zivin & Neidell, 2012), whereas increased levels of ambient particulate matter have been linked to reductions in the performance of warehouse workers (Chang, Graff Zivin, Gross, & Neidell, 2016a), call center staffers (Chang, Zivin, Gross, & Neidell, 2016b), industrial workers (He, Liu, & Salvo, 2016), soccer players (Lichter, Pestel, & Sommer, 2017), and possibly participants in equity markets (Heyes, Neidell, & Saberian, 2016). Together, these findings suggest that air pollution imposes significant societal costs through channels beyond those measurable via administrative mortality and morbidity outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, PM 10 , which consists of fine particulate matter as well as coarse particulate matter, has been linked with the performance of professional football players throughout Germany [12]. After assigning air quality data to the nearest stadium, the authors found that the number of passes per match decreased on days with higher levels of PM 10 .…”
Section: Additional Evidencementioning
confidence: 99%